Maratona e envelhecimento : um olhar para a autoestima - Moreira, Maria Arlene de Almeida (2013)
The longevity became a reality reached by an increasing number of people in worldwide. In a qualitative approach, this study intends to focus on the race, while the sport accessible and inclusive currently practiced by a growing number of people. The rationale of the study is to identify and understand the participation of the seniors in marathon. According to the World Health Organization (WHO), physical activity is a factor that contributes to the quality of life in elderly. Without disregarding others co-factors that influence the quality of life, the study aims to identify the motivational aspects, the feelings and the changes present in different personal, familiar and social contexts of seniors' participation in marathons